Nightbooks - White, J. A. (Katherine Tegen Books, 2019)
Presents a modern twist on "One Thousand and One Nights." Alex loves horror stories and has notebooks full of his own compositions. One day he and some other occupants are trapped in their apartment by a witch and the only way to keep her happy is to tell her one of his stories each night. Soon though, he begins reaching the last pages so he begins making up stories with the help of the other prisoners.